An Unusual Case of Girl With Juvenile Idiopathic Arthritis Later Diagnosed With Systemic Lupus Erythematosus: Diagnostic Challenges in Pediatric Rheumatology - Saja Karaja; Mai Halloum; Joudy Sheikh Taha; Ayham Qatza; Ahmad Alsayadi; Ghofran Al Mansour; Muhannad Abokurshah (Clinical Case Reports)
ABSTRACT This case report underscores the diagnostic challenges in autoimmune diseases, particularly when initial diagnoses are uncertain. A patient initially diagnosed with juvenile Idiopathic arthritis experienced relapse, revealing systemic lupus erythematosus. This highlights the need for ongoing vigilance and careful consideration of alternative diagnoses, even in patients with seemingly clear initial presentations.